Development of energy efficient industrial dryers - Nathan, Kamal G. (2008)
The report presents the work conducted to-date on the development of energy efficient dryers. It includes the computer simulation of Integrated Heat Pump System (IHPS) and experimental stduy of heat pump tumbler and vertical clothes dryers.